Powering beans in Burundi. Seven years of unleashing inclusive bean value chains: 2015-2021 - Nduwarugira, Eric; Ndabashinze, Blaise; Ntukamazina, Jean Nepomuscene; Bararyenya, Astere; Rubyogo, Jean Claude; Katungi, Enid; Mukankusi, Clare; Fungo, Robert; Waswa, Boaz; Kalemera, Sylvia; Kasubri, Fadhili; Birachi, Eliud; et al. (2023)
Over the past seven years (2015-2021), the Pan-Africa Bean Research Alliance (PABRA) and the Institut des Sciences Agronomiques du Burundi (ISABU), supported by the Swiss Agency for Cooperation and Development (SDC) and Global Affairs Canda (GAC), have empowered women to become entrepreneurs in Burundi's bean seed industry. Today, half of Burundi's decentralized bean seed producers are women, resulting in increased food and nutrition security, more bean-based products, and profitable markets for both men and women. Overall, bean production experienced a fivefold increase. The PABRA-ISABU partnership has also catalyzed the development of climate-smart beans and other innovations, such as bean commodity corridors and multistakeholder platforms, that meet the needs of communities. Despite challenges faced by the industry, PABRA and development partners continue to work towards ensuring a food-secure future.